2009
DOI: 10.1158/0008-5472.can-08-2115
|View full text |Cite
|
Sign up to set email alerts
|

A Gonadotropin-Releasing Hormone-II Antagonist Induces Autophagy of Prostate Cancer Cells

Abstract: Gonadotropin-releasing hormone-I (GnRH-I) is known to directly regulate prostate cancer cell proliferation. However, the role of GnRH-II in prostate cancer is unclear. Here, we investigated the effect of the GnRH-II antagonist trptorelix-1 (Trp-1) on growth of PC3 prostate cancer cells. Trp-1 induced growth inhibition of PC3 cells in vitro and inhibited growth of PC3 cells xenografted into nude mice. FITC-N3, an FITCconjugated Trp-1 analogue, was largely present in the mitochondria of prostate cancer cells, bu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 46 publications
(67 reference statements)
4
28
0
Order By: Relevance
“…Nevertheless, GnRH analogues were shown to suppress directly the growth of endometrial, ovarian, breast and prostate tumors and uterine leiomyoma [122,127,128] . Likewise, the growth of prostate cancer cells in vitro and in tumor xenografts was inhibited by activating the GnRH receptor or by GnRH receptor blockade [129] . In line with these observations, phase III trial data have demonstrated that GnRH agonists are effective and well tolerated in the treatment of hormone-sensitive prostate cancer [130] .…”
Section: Gpcrs Activated By Hormonesmentioning
confidence: 99%
“…Nevertheless, GnRH analogues were shown to suppress directly the growth of endometrial, ovarian, breast and prostate tumors and uterine leiomyoma [122,127,128] . Likewise, the growth of prostate cancer cells in vitro and in tumor xenografts was inhibited by activating the GnRH receptor or by GnRH receptor blockade [129] . In line with these observations, phase III trial data have demonstrated that GnRH agonists are effective and well tolerated in the treatment of hormone-sensitive prostate cancer [130] .…”
Section: Gpcrs Activated By Hormonesmentioning
confidence: 99%
“…Certain cellular stresses, such as oxidative stress, nutrient starvation, misfolded protein accumulation, and irradiation could induce autophagy. Recent reports have shown that autophagy is also a cell death mechanism and a response to various anticancer therapies in several types of cancer cells (Chiu et al, 2009;Kim et al, 2009;Liu et al, 2010;Nahimana et al, 2009). Over several decades, the application of natural products has been shown to play an important role in the physiological function of human life, and basic research to develop clinical treatment drugs has a long history.…”
Section: Introductionmentioning
confidence: 99%
“…Antagonist for the type II GnRHR have also been developed and tested in cells expressing rat GnRH (Maiti et al, 2003), human endometrial cells (Fister et al, 2007), and mice (Kim et al, 2009). However, all of these species have lost a functional type II GnRHR (Stewart et al, 2009) and data from these experiments are questionable.…”
Section: Chicken Gnrh-iimentioning
confidence: 99%